Analysis of the advantages of natural resource based economic sub sectors as the basis for regional development policies in Tanah Datar Regency, West Sumatra Province. Issue 1 (October 2021) - Syarif Hidayat, M; Mahyuddin,; Naping, H
Abstract: Tanah Datar is known as an agrarian area with most of the population working in natural resource-based fields, namely agriculture. This is evident in the sectors that play a major role in GRDP, namely the agriculture, forestry and fisheries sectors, but the growth is very small when compared to other sectors. The consequence is seen in the slowdown in the rate of economic growth in Tanah Datar Regency. In addition, the budget allocation for the sector during 2015-2019 was still not a priority and there is still unused agricultural land. This research was conducted to determine the leading sub-sector based on natural resources and the direction of the development of the superior sub-sector spatially in each sub-district in Tanah Datar Regency so that it will later be used as a guideline for policy formulation. The determination of sub-sectors is carried out based on the criteria of competitiveness, basic sector, growth, and sector contribution where each criterion is used shift share analysis method, location quotient (LQ) analysis, growth rate, and sectoral contribution to the next weight obtained compared with the Analytical method. Hierarchy Process (AHP) using Expert Choice 11. The results showed that food crops and horticultural crops were the leading sub-sectors with weights (22.9%) and (14.1%) respectively. Then a spatial development was carried out in the form of mapping in each sub-district according to the superior commodities incorporated in food crops and horticultural crops.